Studies in symbolic interaction. Vol. 30 - Denzin, Norman K. (Bingley : JAI, 2008)
This book emphasizes critical approaches to the study of race, identity and self, as well as developments in interactionist theory, ethics and dramaturical studies.
Includes papers from "Peter M. Hall Lecture series."
Includes bibliographical references.
Description based on print version record.
Keywords: Symbolic interactionism; Social interaction; Interpersonal communication; Social, group or collective psychology; Social interaction; Psychology -- Social Psychology; Language Arts & Disciplines -- Communication Studies; Social Science -- Sociology -- General